Latino and Central American Asylum Seekers in the United States of America During the Trump Administration - Mohammadi, Sina (Cuestiones Políticas, 2020)
The purpose of the article was to examine the Trump administration's asylum policy applied to Central American and Latino applicants. The United States has grappled with refugee problems in recent decades, and in 2018 Trump signed an executive order to detain families seeking to immigrate to the United States without separating from one another. With this decree, a new approach was formed in the policy of the United States government, which emphasizes the severe restrictions on the entry of asylum seekers and immigrants. In the methodological, it is a documentary research close to hermeneutics. It is concluded that, although the United States government has cited security concerns as an excuse to restrict the entry of asylum seekers, especially Latinos from Central American countries, this political approach is in conflict with the national legislation of the United States that stipulates that any citizen Foreigner arriving at any point along the US border, or at official exit points, has the right to apply for asylum. Furthermore, the implementation of such a policy is contrary to the end of the 1951 Convention, which focuses on the protection of refugees without distinction.